Self-Efficacy, Social Support, Academic Flow, and Math Anxiety among Islamic Senior High School Students - Mutia Herawati; Abdul Muhid; Asep Saepul Hamdani (Psympathic : Jurnal Ilmiah Psikologi, 2020)
Math anxiety is a crucial problem experienced by almost all students. Due to the math anxiety affects the decreasing of mathematics achievement, many educators and researchers focused to overcome the math anxiety. The purpose of this study is to empirically examine the effects of math self-efficacy, social support, and academic flow on math anxiety. This research used a quantitative approach, by using psychological scales survey as a data collection. The participants of this study were 167 students which were collected using quota sampling technique at two high schools. The results show that there was a simultaneous significant negative effect of math self-efficacy, social support, and academic flow toward math anxiety. In addition, the partial analysis shows that there is no significant effect between math self-efficacy and math anxiety. While social support and academic flow have a significant effect on math anxiety. Thus, social support and academic flow can be used as strong predictors of math anxiety.